Pengaruh Pemahaman, Sanksi Perpajakan dan Tingkat Kepercayaan Kepada Pemerintah terhadap Kepatuhan Wajib Pajak dalam Membayar PBB-P2 di Kelurahan Ringinanom Kecamatan Nganjuk Kabupaten Nganjuk - Jelita Puji Tricahyani; Indrian Supheni; Dwi Puji Rahayu (AKUNTANSI 45, 2025)
This study aims to analyze the influence of tax understanding, tax sanctions, and the level of trust in the government on taxpayers’ compliance in paying the Rural and Urban Land and Building Tax (PBB-P2) in Ringinanom Village, Nganjuk District, Nganjuk Regency. The research population amounted to 800 taxpayers based on data from the Regional Revenue Agency (Bapenda) of Nganjuk Regency, with a sample of 270 respondents selected using the purposive sampling method. Data analysis was carried out through validity test, reliability test, classical assumption test, multiple linear regression, determination coefficient (R²), t-test, and F test with the help of SPSS software version 22. The results of the study show that partially the understanding of taxation, tax sanctions, and the level of trust in the government have a positive and significant effect on taxpayer compliance. These findings confirm that increasing tax literacy, strict enforcement of sanctions, and public trust in the government are important factors in encouraging taxpayer compliance in fulfilling PBB-P2 payment obligations.